Impact of lipoatrophy on quality of life in HIV patients receiving anti-retroviral therapy - Rajagopalan, Rukmini (Taylor & Francis, 2008)
Metabolic and morphological side-effects occur in HIV-infected individuals receiving anti-retroviral treatment (ART). Peripheral fat loss that occurs particularly in the face, limbs and/or buttocks is referred to as lipoatrophy and has been found to be highly stigmatizing and to adversely impact the health-related quality of life (HRQL). Consumer Health Sciences Survey data collected between November 2003 and January 2006 were utilized to evaluate the impact of lipoatrophy on the HRQL in HIV-infected individuals receiving ART. This was evaluated using analysis of variance with item scores and mental component summary (MCS) and physical component summary (PCS) scores from the Medical Outcomes Trust questionnaire, SF-8 as dependent variables and lipoatrophy as the independent variable controlling for baseline age, sex and ethnicity. Clinical meaningfulness (mean difference divided by population standard deviation, δ/σ) of differences between the groups with and without lipoatrophy was also evaluated. A cohort of 1124 subjects with at least six months of ART was selected based on the availability of data on whether or not lipoatrophy was present. Subjects were primarily male (80%), between the ages of 30 and 60 years (90%), Hispanic (37%) and about 25% each of African American and White. Overall, prevalence of lipoatrophy in this cohort of HIV patients was 18.9%. Statistically significant (p < 0.001) differences in quality of life (as measured by SF-8 individual item scores and MCS and PCS scores) were observed between the two groups. The differences between the groups in item and summary scores were clinically meaningful in the small to near medium range (0.28–0.43). HIV-infected patients already experience a considerable deficiency in HRQL compared to general population; this study demonstrates that lipoatrophy further enhances that negative impact on HRQL.